Twelve new species of Triplocania Roesler (Psocodea: ’Psocoptera’: Ptiloneuridae), from South America - Silva Neto, Alberto Moreira Da; Aldrete, Alfonso N. García; Rafael, José Albertino (Zootaxa, 2016)
Twelve species of Triplocania, seven based on male and female specimens and five based on male specimens, are here described and illustrated; nine species are Brazilian, three are Ecuadorian, and one of the latter is shared with Peru. Comments on sexes known and distribution of the species are included.